Reversal of memory and autism-related phenotypes in Tsc2+/− mice via inhibition of Nlgn1 - Chalkiadaki, Kleanthi; Statoulla, Elpida; Zafeiri, Maria; Haji, Nabila; Lacaille, Jean-Claude; Powell, Craig M.; Jafarnejad, Seyed Mehdi; Khoutorsky, Arkady; Gkogkas, Christos G. (Frontiers in Cell and Developmental Biology, 2023)
Tuberous sclerosis complex (TSC) is a rare monogenic disorder co-diagnosed with high rates of autism and is caused by loss of function mutations in the TSC1 or TSC2 genes. A key pathway hyperactivated in TSC is the mammalian/mechanistic target of rapamycin complex 1 (mTORC1), which regulates cap-dependent mRNA translation. We previously demonstrated that exaggerated cap-dependent translation leads to autism-related phenotypes and increased mRNA translation and protein expression of Neuroligin 1 (Nlgn1) in mice. Inhibition of Nlgn1 expression reversed social behavior deficits in mice with increased cap-dependent translation. Herein, we report elevated translation of Nlgn1 mRNA and an increase in its protein expression. Genetic or pharmacological inhibition of Nlgn1 expression in Tsc2+/- mice rescued impaired hippocampal mGluR-LTD, contextual discrimination and social behavior deficits in Tsc2+/- mice, without correcting mTORC1 hyperactivation. Thus, we demonstrate that reduction of Nlgn1 expression in Tsc2+/- mice is a new therapeutic strategy for TSC and potentially other neurodevelopmental disorders.